Metodologi research - Sutrisno Hadi (Andi, 2004)
ast, jil.1 =c.1 jil.3 =c.1-2 jil.4 =c.1-2 jil.2 =c.1/ tr, jil. 2=c.2/tr, jil.1=c.2-5; jil.2=c.3-4/stoc2, jil.1=c.1-4; jil.2 =c.1; jilid.3 =c.1; jil.4=c.1-2./stoc5.jil.2.c3